2010
DOI: 10.1111/j.2042-7158.2010.01144.x
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance reversal properties and cytotoxic evaluation of representatives of a novel class of HIV-1 protease inhibitors

Abstract: The novel compounds have been shown to be prospective AIDS therapeutics, acting as effective and nontoxic P-gp inhibitors compared with ritonavir, which is a known P-gp inhibitor with unfavourable toxic and P-gp substrate properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Consequently, chemotherapeutic agents exhibit limited minimal interactions with transport proteins such as P-gp are preferred. 98 Conversely, therapeutic agents that competitively inhibit transporters governing efflux may increase victim drug concentrations in relevant organs and tissues (e.g. lymphocytes), thereby enhancing efficacy and decreasing pill burden.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, chemotherapeutic agents exhibit limited minimal interactions with transport proteins such as P-gp are preferred. 98 Conversely, therapeutic agents that competitively inhibit transporters governing efflux may increase victim drug concentrations in relevant organs and tissues (e.g. lymphocytes), thereby enhancing efficacy and decreasing pill burden.…”
Section: Discussionmentioning
confidence: 99%
“…HIV protease inhibitors can increase resistance by inducing overexpression of P-gp in cells, which reduces both toxicity and efficacy of the drug. In contrast, studies showed that an HIV protease inhibitor can play a role as a P-gp blocker (12,14). An HIV protease inhibitor also showed P-gp-inhibitory activity in resistant cancer cells and sensitized them to co-treatment with doxorubicin (19).…”
mentioning
confidence: 99%
“…In our preliminary studies (unpublished data), we found that an HIV protease inhibitor had potential sensitization effects when co-administered with an antimitotic drug. It has been reported that the effectiveness of HIV protease inhibitors correlates with P-gp expression or activity (12)(13)(14)(15)(16)(17). For example, HIV protease inhibitors that are substrates of P-gp can induce resistance in patients with HIV (16,18).…”
mentioning
confidence: 99%